The cost of shift work: Absenteeism in a large German automobile plant. (August 2018) - Frick, Bernd; Simmons, Robert; Stein, Friedrich
Using a balanced panel of some 400 organizational units in a large automobile plant, we analyse changes in absenteeism following a company innovation intended to improve worker health and well-being. During the period under consideration (January 2009–December 2011) the firm replaced its traditional shift schedule associated with high health risks for workers with an ergonomically more advantageous system. Our findings show that this innovation was accompanied by a statistically significant and economically relevant decrease in absenteeism. However, when workers started to express discontent with the new system, management after a few months implemented another shift system that was, from an ergonomical perspective, again associated with higher health risks than those associated with the second one. Absentee figures quickly returned to their initial levels. This suggests that short-term leisure preferences can override long-term health concerns in worker responses to the implementation of different shift schedules.